Controlador de cargas desbalanceadas em sistema de geração fotovoltaica conectado à rede trifásica de distribuição - Brasil, Francisco Carlos Leite (2021)
This work consists of a control strategy for unbalanced loads, based on a system consisting of a proposed three-phase Phase-Locked Loop - PLL, a power control and the One Cycle Control - OCC technique. Such a strategy has as methodology the control of power, from the input resistance and the positive sequence component of the load current. The three phase PLL is used to track the phase and frequency, and the OCC modulator from the conventional OCC. The control system was implemented in a simulation environment using the PSCAD / EMTDC software, with the following technical characteristics: nominal power of 1 kVA; rated voltage of 220 V; line inductance equal to 0,2 mH; RL load (50 Ω and 2 mH) and frequency of 60 Hz. As a way of evaluating the performance of the system, several simulations were carried out with the implementation of disturbance events in the network, verifying its behavior during the transient and stationary regime. In such work, it is intended to achieve the following goals: 1) to implement the OCC technique as part of the control system; 2) obtain symmetrical and continuous load currents during disturbance events in the network with harmonic distortion levels within the regulatory limits, and 3) maintain the active and reactive power constant in the load during the transient and stationary regime when the occurrence of network disturbances.